ANALYSIS OF KAYAT TRADITION SHIFTING IN KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI - Titi Indrawati; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of this study was the aesthetic concept of kayat tradition shifting, from before implamantation up to the implamantation of kayat in Kecamatan Kuantan Hilir Seberang Kabupaten Kuantan Singingi. The purpose of the study was to know the aspects of kayat tradition shifting in Kecamatan Kuantan Hilir Seberang Kabupaten Kuantan Singingi. The population of this studyis was society that they domiciled in Kecamatan Kuantan Hilir Seberang Kabupaten Kuantan Singingi numbered 12.771 people. The technique of collecting data was qualitative descriptive analysis, purposive sampling. The sampling of this study was 80 people .the kind of this study was descriptive qualitative. Technic of collecting data was collected by observation, interview, questionnaire, documents and bibliography. Data analysed by descriptive kualitative passes through percentage. Of respondent answer percentage count as a whole acquired Yes answer as much 55,4% one lays in rank 50,01%-100%. Hypothesis thus that aspects of kayat tradition shifting in Kecamatan Kuantan Hilir Seberang Kabupaten Kuantan Singingi was accepted. Base observational result, therefore gets to be concluded that kayat tradition in Kecamatan Kuantan Hilir seberang Kabupaten Kuantan Singingi which is gets shifting.Key words : Shifting, Kayat Tradition.